Lipid vesicles trigger α-synuclein aggregation by stimulating primary nucleation - Galvagnion, Céline (Nat Chem Biol, 2015)
α-synuclein (α-syn) is a 140-residue intrinsically disordered protein that is involved in neuronal and synaptic vesicle plasticity but its aggregation to form amyloid fibrils is the hallmark of Parkinson’s disease (PD). The interaction between α-syn and lipid surfaces is believed to be a key feature for mediation of its normal function but under other circumstances is able to modulate amyloid fibril formation. Using a combination of experimental and theoretical approaches, we have identified in this study the mechanism through which facile aggregation of α-syn is induced under conditions where it binds to a lipid bilayer, and we show that the rate of primary nucleation can be enhanced by three orders of magnitude or more under such conditions. These results reveal the key role that membrane interactions can play in triggering conversion of α-syn from its soluble state into the aggregated state that is associated with neurodegeneration and to its associated disease states.